Clinical diagnosis and treatment of a patient with hypertension, hypokalemia, and bilateral adrenal adenomas - Zhang, Tingting; Chen, Tao; Zhang, Wenjie; Tan, Lu; Li, Li; Zhu, Yuchun; Ren, Yan (Frontiers in Endocrinology, 2025)
Aldosterone-producing adenoma (APA) is one of the main types of primary aldosteronism (PA). APAs are predominantly unilateral, whereas bilateral APAs are rare. Currently, clinical experience in the diagnosis and treatment of bilateral APAs is limited, posing significant challenges. This article reports the case of a PA patient with bilateral adrenal nodules. Adrenal venous sampling (AVS) revealed no dominant lateral secretion, but 68Ga-Pentixafor PET/MR imaging, which targets CXCR4, revealed bilateral positive lesions. The patient achieved biochemical and clinical remission after undergoing bilateral partial adrenalectomy, and CYP11B2 immunohistochemical staining confirmed that both nodules were APAs. This case report suggests that 68Ga-Pentixafor nuclear imaging, which targets CXCR4, is a noninvasive and reliable method for PA subtyping and may be the optimal method for the definitive diagnosis of bilateral APA. Bilateral partial adrenalectomy may be an effective and safe surgical procedure for the treatment of bilateral APAs. This study provides new insights and considerations for clinicians in the diagnosis and treatment of bilateral APAs.